Pengaruh Pemahaman K3 dan Ketaatan SOP terhadap Tingkat Kecelakaan Kerja - Ismoko, Ismoko; Asmoro, Eddi Indro; Hidayat, Zainal Imron (Universitas Ivet, 2023)
Working on a ship might make people see something more than others, for example, high salaries continue to be able to go see new places for free and so on. The author who is a ship captain must be able to provide a sense of security to his crew, manage crews who come from various countries which of course have different characteristics and so on. However, the most important thing here is how can a captain be able to compliance and provide understanding to his subordinates about understanding SOP so that work accidents can be minimized. Referring to the above, here I am conducting research on understanding K3 and observing SOPs on the level of work accidents on Swissco Garnet ships, the company Allianz Shimanagement LLC. The research method here I use a quantitative approach with explanatory research. The results of the study show that compliance with OSH and understanding of SOP is closely related to the level of work accidents on the AHTS Swissco Garnet ship in the company Allianz SHipmanagement LLC. And it is hoped that from the results of this study the author can provide an understanding to the crew that understanding K3 and complying with the SOP that has been made by the company is also a tool that can prevent someone from work accidents.